Recent Advances in Producing Sugar Alcohols and Functional Sugars by Engineering Yarrowia lipolytica - Abbasi, Abdul Rahman; Liu, Jinle; Wang, Zhi; Zhao, Anqi; Ying, Hanjie; Qu, Lingbo; Alam, Md. Asraful; Xiong, Wenlong; Xu, Jingliang; Lv, Yongkun (Frontiers in Bioengineering and Biotechnology, 2021)
The sugar alcohols and fuctional sugars have wide applications in food, pharmaceutical, and chemical industries. However, the smaller quantities of natual occuring sugar alcohols and functional sugars restricted their applications. The enzymatic and whole cell catalyst production is emerging as the predominant alternatives. The properties of Yarrowia lipolytica make it a promising sugar alcohol and functional sugar producer. However, there are still some issues to be resolved. As there existing reviews about the chemical structures, physicochemical properties, biological fuctions, applications, and biosynthesis of sugar alcohols and/or functional sugars in Y. lipolytica, this minireview will not only update the recent advances in enzymatic and microbial production of sugar alchols (erythritol, D-threitol, and xylitol) and functional sugars (isomaltulose, trehalose, fructo-oligosaccharides, and galacto-oligosaccharides) by using recombinant Y. lipolytica, but also focus on the studies of gene discovery, pathway engineering, expanding substrate scope, bioprocess engineering, and novol breeding methods to resolve the aforementioned issues.